2020
DOI: 10.1002/advs.202000675
|View full text |Cite
|
Sign up to set email alerts
|

Generalizable, Reproducible, and Neuroscientifically Interpretable Imaging Biomarkers for Alzheimer's Disease

Abstract: Precision medicine for Alzheimer's disease (AD) necessitates the development of personalized, reproducible, and neuroscientifically interpretable biomarkers, yet despite remarkable advances, few such biomarkers are available. Also, a comprehensive evaluation of the neurobiological basis and generalizability of the end‐to‐end machine learning system should be given the highest priority. For this reason, a deep learning model (3D attention network, 3DAN) that can simultaneously capture candidate imaging biomarke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 60 publications
1
44
0
Order By: Relevance
“…These results further suggested that gene expression can be reflected by R2SNs. In brief, R2SNs have a genetic basis, and the present findings provide the possibility of estimating the risk of a gene by using R2SNs and indicate a certain degree of evidence for genetic disease research, such as that conducted regarding AD (Jin et al, 2020b;Zhao et al, 2020).…”
Section: Discussionmentioning
confidence: 60%
“…These results further suggested that gene expression can be reflected by R2SNs. In brief, R2SNs have a genetic basis, and the present findings provide the possibility of estimating the risk of a gene by using R2SNs and indicate a certain degree of evidence for genetic disease research, such as that conducted regarding AD (Jin et al, 2020b;Zhao et al, 2020).…”
Section: Discussionmentioning
confidence: 60%
“…First, the sample size of the in-house dataset was relatively small, particularly for the WMH-MCI group, and the sizes of the WMH-MCI and WMH-nCI groups were unbalanced due to the study design, which may lead to lower statistical power. Based on studies focused on the neuroimaging features of AD [ 71 , 72 ], the characteristic GM alteration pattern in WMH patients with MCI needs further cross-validation by large-scale multi-center studies in the future. Second, we did not conduct a comprehensive evaluation of motor and mood disturbances which are common in patients with WMH.…”
Section: Discussionmentioning
confidence: 99%
“…The development of personalized, reproducible, non-invasive, and neuroscientifically interpretable biomarkers are urgently needed for AD precision medicine (16,42), yet despite remarkable advances, few such biomarkers are available. Neuroimaging using DTI and fMRI in conjunction provides objective information on the structure and function that for assessing network connectivity of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning is an application of artificial intelligence that allows computers to learn automatically and improve from experience. It is one of today's most rapidly growing technical fields (13), which performs throughout science including health care (14) such as identification and classification for diseases like AD (15)(16)(17), traffic programming (18), and marketing apps designing (19), which allows us to process largescale, multidimensional, complex datasets in this information explosion of an era. Machine learning-based analysis of connectomic data created from neuroimaging studies in patients AD has been extensively studied in the literature (5,9,12,20,21).…”
Section: Introductionmentioning
confidence: 99%